Enhancing Employee Performance through Career Development, Training, and Human Resource Planning: The Mediating Effect of Motivation - Ani Juwita Handayani; Edi Sugiono; Suryono Efendi; Hasanudin (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Veterinary hospitals play a vital role in ensuring animal health, but their success depends on skilled and motivated veterinarians. This research investigates how career development, training, and human resource planning influence veterinarian performance, with employee motivation as a mediating factor, in a veterinary hospital in DKI Jakarta. The objective is to understand these relationships and provide practical recommendations for improving service quality. A quantitative approach was used, collecting data from 125 veterinarians through questionnaires and interviews. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to analyze the data. The findings show that career development, training, and human resource planning positively and significantly enhance performance, both directly and through motivation, which acts as a key mediator. All hypotheses were supported, confirming the importance of these factors in boosting veterinarians’ effectiveness. In conclusion, veterinary hospitals should prioritize structured career paths, regular training, and strategic planning to enhance motivation and performance, improving animal care quality. However, the study’s reliance on self-reported data and focus on DKI Jakarta may limit its applicability to other contexts.